Absolutely Right and Relatively Good: Consequentialists See Bioethical Disagreement in a Relativist Light. Issue 3 (3rd July 2021) - Viciana, Hugo; Hannikainen, Ivar R.; Rodríguez-Arias, David
Abstract: Background: Contemporary societies are rife with moral disagreement, resulting in recalcitrant disputes on matters of public policy. In the context of ongoing bioethical controversies, are uncompromising attitudes rooted in beliefs about the nature of moral truth? Methods: To answer this question, we conducted both exploratory and confirmatory studies, with both a convenience and a nationally representative sample (total N  = 1501), investigating the link between people's beliefs about moral truth (their metaethics) and their beliefs about moral value (their normative ethics). Results: Across various bioethical issues (e.g., medically-assisted death, vaccine hesitancy, surrogacy, mandatory organ conscription, or genetically modified crops), consequentialist attitudes were associated with weaker beliefs in an objective moral truth. This association was not explained by domain-general reflectivity, theism, personality, normative uncertainty, or subjective knowledge. Conclusions: We find a robust link between the way people characterize prescriptive disagreements and their sensibility to consequences. In addition, both societal consensus and personal conviction contribute to objectivist beliefs, but these effects appear to be asymmetric, i.e., stronger for opposition than for approval.